2019
DOI: 10.1371/journal.pone.0226952
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal control of dry fomites on regulating the survival of human pathogenic bacteria responsible for nosocomial infections

Abstract: We monitored the survival of human pathogenic bacteria [Escherichia coli (ATCC), extended-spectrum β-lactamase-producing E. coli (Clinical isolate), New Delhi metallo-β-lactamase-producing E. coli (clinical isolate), Staphylococcus aureus (ATCC)] on dry materials (vinyl chloride, aluminum, plastic, stainless steel) at distinct temperatures (room temperature or 15°C–37°C). These bacteria favored a lower temperature for their prolonged survival on the dry fomites, regardless of the material type. Interestingly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
1
12
0
2
Order By: Relevance
“…While C. albicans did persist for more than 1 h on stainless steel and for a maximum of 60 min on nordic gold, the fungus persists for only 5 min and 30 min on copper and cupronickel respectively [ 190 ]. Other studies on stainless steel revealed a persistence capability of more than 24 h to 7 days at RT [ 191 , 192 ] and persistence of less than 6 h at body temperature [ 193 ]. In contrast to copper, silver impregnation did not work as a fungicide against C. albicans , as comparison of C. albicans persistence on a polymer being silver impregnated or not reveal no difference and survival in both cases has been at least 7 days [ 105 ].…”
Section: Resultsmentioning
confidence: 99%
“…While C. albicans did persist for more than 1 h on stainless steel and for a maximum of 60 min on nordic gold, the fungus persists for only 5 min and 30 min on copper and cupronickel respectively [ 190 ]. Other studies on stainless steel revealed a persistence capability of more than 24 h to 7 days at RT [ 191 , 192 ] and persistence of less than 6 h at body temperature [ 193 ]. In contrast to copper, silver impregnation did not work as a fungicide against C. albicans , as comparison of C. albicans persistence on a polymer being silver impregnated or not reveal no difference and survival in both cases has been at least 7 days [ 105 ].…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, the length of bacterial survival in the environment impacts the risk of spread. The corresponding time frame depends on multiple factors among them the bacterial species [ 5 ] and overall bioburden [ 6 , 7 ], the source of isolation [ 5 ], the type of surface material [ 8 , 9 ], the ambient temperature [ 8 , 10 13 ], the extent of UV radiation [ 14 ], the local pH [ 13 ], the relative air humidity [ 8 , 11 ], the availability of water and nutrients [ 8 ], the presence of chemical noxa [ 15 ], the company by additional (concurrent) bacterial species [ 11 ] and other factors like pigmentation [ 16 ], and biofilm formation [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many pathogens are more stable on colder fomites than in warmer conditions. 5 Of particular relevance in the current SARS-CoV-2 outbreak is the stability of other coronaviruses, which survive on fomites for longer periods at lower temperatures. 6 In addition, food is often eaten on site, with some events promoted by communal free food such as pizza.…”
Section: Climbing Gyms As Possible High-risk Transmission Locations In Microbial Outbreaksmentioning
confidence: 99%
“…abdominal thrusts (Heimlich maneuver), which were at one time recommended for the initial resuscitation of drowning patients, are currently discouraged. 5 As you alluded to, the evidence concerning the actual volume and effect of water aspiration are murky at best; additionally, many of the studies done in animals have used forced aspiration of large volumes, which may not be applicable to humans. The prevalence of laryngospasm, as well as differences in fluid shifts due to water salinity, are also not well understood.…”
mentioning
confidence: 99%